Intelectuais, literatura e imprensa no pós-golpe - Czajka, Rodrigo [UNESP] (My University, 2014)
Culture and the arts in Brazil were impacted directly by the military coup from 1964 onwards. In spite of repression and censorship, the activity of intellectuals and artists in the pre-1964 period was not interrupted nor became stagnant, but gained even greater force due to the presence of control and restrictions by the institutions of repression over against the freedom of creation and thought. As in many sectors of cultural production, literature played a vigorously combative role against the arbitrariness of the regime and implemented “projects of resistance” on the basis of key elements of representation. This occurred, for instance, through the writing and circulation of works such as Pessach: a travessia, by journalist Carlos Heitor Cony, and Quarup, by journalist Antonio Callado. The two novels enabled a broad debate on the narrative form and the scope of involvement in the literature of the 1960s, such as the confrontation between Paulo Francis and Ferreira Gullar in the pages of Revista Civilização Brasileira, which is the focus of this article.

A cultura e as artes sofreram os impactos diretos do golpe militar sobre suas produções, a partir de 1964. Apesar da repressão e da censura, a atividade de intelectuais e artistas no pré-1964 não foi interrompida ou estagnada, mas assumiu força ainda maior em virtude da presença do controle e do cerceamento dos órgãos de repressão frente à liberdade de criação e de pensamento. Como em muitos setores da produção cultural, a literatura assumiu um papel fortemente combativo das arbitrariedades do regime e se destacou ao colocar em pauta “projetos de resistência” a partir de elementos-chave de representação, tal como transcorreu na elaboração e circulação das obras Pessach: a travessia, de autoria do jornalista Carlos Heitor Cony, e Quarup, de autoria do jornalista Antonio Callado. Os dois romances propiciaram um amplo debate sobre a forma narrativa e os alcances do engajamento na literatura da década de 1960, a exemplo dos embates entre Paulo Francis e Ferreira Gullar, nas páginas da Revista Civilização Brasileira, que serão tematizados neste artigo.
Intellectuals, literature and press in post-coup period